Strand Monitoring and Anthropological Surveys Provide Insight into Marine Turtle Bycatch in Small-Scale Fisheries of the Eastern Mediterranean - Snape, Robin T. E.; Beton, Damla; Broderick, Annette C.; Cicek, Burak A.; Fuller, Wayne J.; Ozden, Ozge; Godley, Brendan J. (Allen Press Inc, 2013)
It has become widely recognized that a large gap exists in the global knowledge of fisheries due to the continued oversight of the small-scale sector. For populations of marine turtles restricted to the eastern Mediterranean, bycatch in small-scale fisheries is a concern. By using North Cyprus as a case study for the region, we used anthropological methods to estimate the magnitude of marine turtle bycatch, while presenting novel information on the marine turtle life stages using the coast and profiling the fishery itself. Our analyses suggest that as many as 1000 turtles may be caught annually by this fishery with an estimated mortality rate of 60%. Trammel nets were the main cause of marine turtle bycatch. Strandings coincided with setting of trammel nets that target siganids (Siganus luridus and Siganus rivulatus) and the majority of bycatch registered by fishers were caught in these gear types. We demonstrate a relatively simple approach to evaluating marine turtle bycatch, providing information that will allow local authorities and conservation groups to direct further research and possible mitigation measures.
Keywords: small-scale fisheries; artisanal fisheries; marine turtle; bycatch; trammel net; stranding; Mediterranean